Motives for Saudi Women to Exercise Sports Activities – A Field Study on Women Who Are Used to Going to Sports Clubs in Hofuf City, Al-Ahsa Governorate 2020 – - Al-Naiem, Luluh AbdulHameed (Journal of Humanities & Social Sciences, 2021)
This study aimed to identify the most important motivations for women going to sports centers in the city of Al-Ahsa. The study used the method of social survey, and used a questionnaire. The study was applied on 150 women using a simple random sample. The questionnaire was divided into three main axes, namely psychological determinants, health determinants and social determinants. The study concluded the following results: There are statistically significant differences in the level of motivations of women practicing sport according to the age variable (less than 0.05) and the educational level, and that there are no differences in the level of women’s motivations to practice sports according to the variable of social status. The study showed that the most effective factors in women going to sports centers are psychological, then health motives, and finally social motives, given the perceptions of society towards women’s roles. The current study showed that sport brings many benefits to women not only for health considerations, but also includes psychological, social and aesthetic aspects. The study has also shown that sports provide women with the energy necessary to face life’s difficulties to find their way and raise the quality of their lives and enable them to efficiently manage their multiple roles.